2017
DOI: 10.1371/journal.pone.0171407
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV status and its impact on the loss in the follow-up of HIV-infected patients on potent anti-retroviral therapy programs in a (post-) conflict setting: A retrospective cohort study from Goma, Democratic Republic of Congo

Abstract: BackgroundThe study aimed to identify the impact of non-disclosure of HIV status on the loss to follow-up (LTFU) of patients receiving anti-retroviral therapy.MethodologyA historic cohort of HIV patients from 2 major hospitals in Goma, Democratic Republic of Congo was followed from 2004 to 2012. LTFU was defined as not taking an ART refill for a period of 3 months or longer since the last attendance, and had not yet been classified as ‘dead’ or ‘transferred-out’. Kaplan-Meier plots were used to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
3
35
3
Order By: Relevance
“…We did not have the possibility to assess those data, or to assess social support from the family and the community, and HIV status disclosure. We also did not show differences according to social data such as educational level contrary to what has been shown in studies of LTFU risk factors [8,41]. However, difficulties to return to care when living more than 5 km to the care centre in the regions could be due to financial or transportation issues.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…We did not have the possibility to assess those data, or to assess social support from the family and the community, and HIV status disclosure. We also did not show differences according to social data such as educational level contrary to what has been shown in studies of LTFU risk factors [8,41]. However, difficulties to return to care when living more than 5 km to the care centre in the regions could be due to financial or transportation issues.…”
Section: Discussioncontrasting
confidence: 89%
“…Among those PLHIV lost to follow-up, 3,650 were lost to followup before 12/31/2013 and were included in this study (Fig 2). The study included 2,380 (65%) women and median (interquartile range [IQR]) age was 35 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The most prescribed initial ART regimen contained zidovudine (AZT) or stavudine (d4T) and lamivudine (3TC) plus nevirapine (NVP) or efavirenz (EFV) for 2,958 (81%) individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Participants also noted that disclosure concerns made them reluctant to ask friends or family for instrumental support that would have helped them stay in HIV care. Our results are in keeping with findings from India, in which disclosure avoidance has been associated with delays in seeking HIV care, 20 and with findings in other LMICs, in which nondisclosure of serostatus has been associated with negative outcomes including poor mental health and reduced quality of life, 21,22 loss to care, 23 and virological failure. 24 In this study, disclosure concerns, together with perceptions of poor quality of care and lack of respect, also had discouraged participants from seeking care in the public sector.…”
Section: Discussionsupporting
confidence: 90%
“…who identified competing social and economic demands, violence, lack of family or community support, and dissatisfaction with care . Several studies have identified HIV‐related stigma as a barrier to accessing ART or retention in care . Fear of violence and/or rejection by a partner is commonly reported as a barrier to accessing HIV care, particularly for women.…”
Section: Discussionmentioning
confidence: 99%